John L. Smithmeyer memorandum - Smithmeyer, John L., -1908.
Holograph memorandum concerning the construction of public buildings.
Architect.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Public buildings -- Design and construction; Architects